Preparation of the individual diastereomers of adenylyl-(2'-5')-P-thioadenylyl-(2'-5')-adenosine and their 5'-phosphorylated derivatives. - de Vroom, E (1987)
The individual diastereomers of trimer A2'p5'A2'p(s)5'A, containing one phosphorothioate linkage, were prepared via a modified hydroxybenzotriazole phosphotriester approach. The 5'-phosphorylated derivatives of the latter compounds were obtained after phosphorylation with a 6-trifluoromethyl-1-benzotriazolyl activated phosphoromorpholidate.